Aportes de género a la salud sexual y reproductiva - Ragúz, María (1995)
This article is about research on the meaning of Gender-Man, Masculinity, Woman, and Femininity- in an accidental sample of children, youngsters, adults, and elders from different low SES groups in Lima, Perú. Through content analysis of open interviews it is shown that, for these groups, sex and gender are not being differentiated. Results are interpreted in terms of the implications these conceptualizations of gender have for sexual and reproductive health program interventions, like in family planning, assertiveness training, sex education, women empowerment workshops, male masculinity workshops, and women' s assertiveness training and awareness raising programs, as well as interventions in domestic violence and prevention of sexual abuse. The need to trascend gender roles, which sustain gender relations of power and submission in peruvian society, is strongly stressed.